2020
DOI: 10.3390/atmos11121362
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Surface Fluxes in the ECMWF Land Surface Model to the Remotely Sensed Leaf Area Index and Root Distribution: Evaluation with Tower Flux Data

Abstract: The surface-atmosphere turbulent exchanges couple the water, energy and carbon budgets in the Earth system. The biosphere plays an important role in the evaporation process, and vegetation related parameters such as the leaf area index (LAI), vertical root distribution and stomatal resistance are poorly constrained due to sparse observations at the spatio-temporal scales at which land surface models (LSMs) operate. In this study, we use the Carbon Hydrology Tiled European Center for Medium-Range Weather Foreca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 66 publications
(91 reference statements)
0
16
0
Order By: Relevance
“…In fact, the calibration of model parameters is paramount, as the current model configuration has been tuned based on an outdated land cover data set. As an example, Stevens et al (2020) investigated the close relationship between LAI and the minimum stomatal resistance and rooting depth in CHTESSEL showing some potential to improve the latent heat flux variability via an adjustment of these parameters. However, those results were based on offline simulations for 17 flux towers.…”
Section: Open Regional Issues and Future Directionsmentioning
confidence: 99%
“…In fact, the calibration of model parameters is paramount, as the current model configuration has been tuned based on an outdated land cover data set. As an example, Stevens et al (2020) investigated the close relationship between LAI and the minimum stomatal resistance and rooting depth in CHTESSEL showing some potential to improve the latent heat flux variability via an adjustment of these parameters. However, those results were based on offline simulations for 17 flux towers.…”
Section: Open Regional Issues and Future Directionsmentioning
confidence: 99%
“…This may induce changes to traditional watering crop strategies, harvesting periods, pest management, or even crop culture replacements. Likewise, insurance (and reinsurance) companies need reliable historical data to assess the risk of severe droughts or flooding (Tadesse et al, 2015;Jensen and Barrett, 2016), in particular for smallholder agriculture. For public and private stakeholders, offline land surface datasets can provide complementary information needed to support decision makers.…”
Section: Introductionmentioning
confidence: 99%
“…This uniform distribution replaces the current exponential formulation and depends only on the maximum rooting depth (R DMAX ). This root distribution formulation was investigated by Stevens et al [48] and showed potential for improvement of the water and energy fluxes. The transformation of root zone soil moisture to water stress is also an open question, and there are different approaches to relate root zone soil moisture and the water stress factor [49,50].…”
Section: Updated Soil Parametrizationmentioning
confidence: 99%